2016
DOI: 10.1097/id.0000000000000327
|View full text |Cite
|
Sign up to set email alerts
|

Crestal Approach to Sinus Floor Elevation for Atrophic Maxilla Using Platelet-Rich Fibrin as the Only Grafting Material

Abstract: This prospective study showed that platelet-rich fibrin promoted endosinus bone gain when used as the grafting material in the crestal approach to sinus floor elevation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 24 publications
4
48
0
1
Order By: Relevance
“…Studies have shown that PRF has greater osteogenic ability, involves a simple preparation process, is devoid of extrinsic biological agents, and has sustained release of growth factors [5]. Previous studies have revealed the potential of PRF to promote endosinus bone regeneration [3,4] and to reduce healing time after sinus floor elevation [5]. In our case bone height and density were significantly improved with the use of hydroxyapatite and PRF membrane.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Studies have shown that PRF has greater osteogenic ability, involves a simple preparation process, is devoid of extrinsic biological agents, and has sustained release of growth factors [5]. Previous studies have revealed the potential of PRF to promote endosinus bone regeneration [3,4] and to reduce healing time after sinus floor elevation [5]. In our case bone height and density were significantly improved with the use of hydroxyapatite and PRF membrane.…”
Section: Discussionsupporting
confidence: 56%
“…The sinus augmentation procedure provides a way to increase the amount of available bone and the placement of longer implants [1].The advantage of using Platelet rich fibrin (PRF) is that it has increased osteogenic ability, a simple preparation process, absence of extrinsic biological agents, and sustained release of growth factors [2].There are many studies conducted to reveal the potential of PRF to promote endosinusbone regeneration [3], [4]and to reduce healing time after sinus floor elevation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Six references (16,17,(19)(20)(21)(22) reported bone gains ranging from 1.8 to 5.7 mm using a crestal approach with no graft placement. Deviations in reporting and data collection prevent a meaningful statistical analysis other than noting the consistency of results.…”
Section: Crestal Osteotome Approach For Sinus Elevationmentioning
confidence: 98%
“…Maintenance of the space created after membrane elevation may be important for bone formation to occur (15)(16)(17)(18)(19)(20). The decision to use an osteotome method via the crestal approach allows elevation of the membrane with or without graft placement, which can result in adequate bone function for long-term implant success (7).…”
Section: Crestal Osteotome Approach For Sinus Elevationmentioning
confidence: 99%
See 1 more Smart Citation